Impact of Irrigation Regimes on Growth and Postharvest Quality of Pomegranates (Punica granatum L.) under Conditions of Newly Reclaimed Land - Magdi A.A. Mousa; Adel D. Al-Qurashi; Omer H.M. Ibrahim; Kamal A.M. Abo-Elyousr; Ahmed M.K. Abdel Aal; Abdel-Fattah M. El-Salhy; Tarek K.H. El-Bolok; Mohamed A.H. Ali; Esmat F. Ali; Eman A.A. Abou-Zaid (HortScience)
Farmers are encouraged to invest in crops that will grow and produce under the predicted climate change, such as global warming, limited water supplies, and drought-imposed water restrictions on agriculture. The drought-tolerant pomegranate (Punica granatum L.) is a promising horticulture crop that can be grown under arid conditions. To successfully implement irrigation management strategies in orchards, knowledge of plant responses to water deficits, tree shoot and fruit growth patterns, and irrigation management strategies that conserve water is required. The present study described the response of pomegranate trees of the Manfalouty variety to deficit irrigation under the local climate. The experiment was conducted during the 2020 and 2021 seasons. The experiment was carried out on a private farm in the Bani Uday district of Manfalouty, Assiut Governorate, Egypt. Eighteen trees with comparable strength and growth were chosen, free of elemental deficiency signs, planted at 3.5 × 3.5 m, with an age of 8 years. Three irrigation levels 50%, 75%, and 100% of the pomegranate tree’s water standard were applied. With the randomized complete block design (RCBD), each treatment was used three times, with two trees in each iteration. Results revealed that applying irrigation at a rate of 75% enhanced fruit quality and yield, mitigated sun sting and cracking, and improved vegetative growth. Moreover, water use efficiency (WUE) was increased, which was reflected in the increase of the percentage of commercial and marketing fruits and decreased production costs when applying 75% of the water ration, which maintains soil and natural resources for sustainable agriculture.